Bio-diversified integrated natural farming – a success story - Singh, B P; Khode, Narendra; Singh, Ranjit (Indian Farming, 2018)
Besides livestock and poultry, Mr Lakra is cultivating cereal crop (wheat, rice) oilseeds crop (mustard), legume fodder like berseem clover, vegetables like pumpkin, spinach, Drumstick, Kundru etc., fruits plants like banana, papaya, datepalm, pindara, sapota, pears, orange, lemon, mango, coconut, water apple, custard apple, fig, star fruit, jamun, guava etc spices like dalchini, tej Patta, turmeric, etc along with teak, arjun, tapioca trees. Biodiversity is being maintained in reality with utmost care of each and every plant and animal at his farm.